Sinkretisme dalam adat masyarakat Bajau di Sabah - Syamsul Azizul Marinsah,; Mohd Anuar Ramli, (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2017)
The spread of Islam in the Archipelago especially in Sabah has produced two forms of interactions which are Islamization and sincretizing. Islamization process that occured subtly and gradually at that time caused Bajau community easy to accept Islam without being forced. However, there are some practices of Bajau community that closely linked to the animism belief still being practiced to produced a process of syncretism. The objective of this article is to introduce Islamic methods by suggesting guidelines or legislation parameter in interacting with syncretism in traditions of Bajau community in Sabah. In facing syncretism between the traditional practices of Bajau with the teaching of Islam, there are at least three Islamic approaches towards the developed culture among Bajau community which are to accept, modify or reject. Therefore, an appropriate method of Islamic law need to prevail to handle the phenomenon in ensuring the balance between idealism contained in Islamic law with the reality of its implemantation in Bajau community. The study found that there are many symptoms of syncretism occured in tradition and culture of Bajau community which are difficult to know whether it is a genuine Islamic teachings or a relic of pre-Islamic tradition.